2020
DOI: 10.1111/cas.14508
|View full text |Cite
|
Sign up to set email alerts
|

Highly expressed tumoral emmprin and stromal CD73 predict a poor prognosis for external auditory canal carcinoma

Abstract: Squamous cell carcinoma of the external auditory canal (SCC‐EAC) is rare and has a poor prognosis. The SCC‐EAC cases with high‐grade tumor budding (TB) or poorly differentiated clusters (PDCs) are associated with shorter survival than those with low‐grade TB or PDCs. Extracellular matrix metalloproteinase inducer (emmprin) is a protein expressed in tumor cells that stimulates the production of MMP‐2 by stromal fibroblasts to facilitate tumor invasion. Recently, we reported that emmprin forms a complex with CD7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Furthermore, high tumoral emmprin and stromal CD73 expression cases were significantly associated with middle cranial fossa invasion and disease recurrence. In vitro analyses confirmed the complex formation between emmprin and CD73, the more abundant production of MMP-2 coming from fibroblasts co-cultured with TBSCC cells than from those cultured alone, and the reduction in MMP-2 production by the transfection of CD73 siRNA into fibroblasts co-cultured with tumor cells [15].…”
Section: Ecm Degradationmentioning
confidence: 66%
See 1 more Smart Citation
“…Furthermore, high tumoral emmprin and stromal CD73 expression cases were significantly associated with middle cranial fossa invasion and disease recurrence. In vitro analyses confirmed the complex formation between emmprin and CD73, the more abundant production of MMP-2 coming from fibroblasts co-cultured with TBSCC cells than from those cultured alone, and the reduction in MMP-2 production by the transfection of CD73 siRNA into fibroblasts co-cultured with tumor cells [15].…”
Section: Ecm Degradationmentioning
confidence: 66%
“…More recently, Aoki et al [56] reported that extracellular matrix metalloproteinase inducer (emmprin) forms a complex with CD73, a cell surface protein regulating adenosinergic signaling and involved in tumor invasion processes. Subsequently, the same group [15] studied 34 pretreatment biopsy specimens of primary TBSCC, and reported an association between high tumoral emmprin expression and high-grade tumor budding, and between high stromal CD73 expression and high-grade PDCs. Concurrent elevated expression of tumoral emmprin and stromal CD73 was an independent poor prognostic factor for overall survival (OS) in multivariate analysis.…”
Section: Ecm Degradationmentioning
confidence: 99%
“…treatment strategy in this field, accumulation of evidence related to an appropriate staging system and a variety of prognostic factors are desired. Reported prognostic factors include disease stage, surgical margin, 2,3 molecular markers, 6,7 and affected anatomical markers. 8 Recently, inflammation-based factors, represented by the ratio of the absolute inflammatory cell counts in peripheral blood cells (NLR, PLR, and LMR), have been reported as markers for predicting the pretreatment prognosis of various solid tumors, including head and neck SCCs.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, molecular biological features, such as extracellular matrix metalloproteinase inducer (emmprin), CD73, and laminin5-gamma2 are associated with poor survival. 6,7 Furthermore, with regard to the extent of anatomical invasion, the destruction of the middle ear ossicles is also linked to poor survival. 8 The systemic inflammatory response plays a key role in malignant tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, high levels of CD73 expression by CAF promote cancer cells proliferation ( 86 ) and are associated with poor prognosis in different cancers like CRC ( 81 ), prostate cancer ( 89 ), Squamous cell carcinoma of the external auditory canal (SCC-EAC) or nonmuscle invasive bladder cancer ( 89 , 90 ).…”
Section: Direct Expression Of Iicps By Cafsmentioning
confidence: 99%